THE CORRELATION BETWEEN DIGITAL LITERACY AND ENGLISH READING COMPREHENSION AMONG SENIOR HIGH SCHOOL STUDENTS - Agustiani Wijayanti; Yeni Rahmawati; Khusnul Khatimah (Edukasi: Jurnal Pendidikan, 2026)
This research investigated the association between digital literacy and English reading proficiency among senior high school students within a technology-supported learning context. Using a quantitative correlational approach, the study involved 59 eleventh-grade students from a public high school in East Kalimantan who were selected through simple random sampling. Data collection employed two instruments: a digital literacy survey and an English reading comprehension assessment. The collected data were processed using both descriptive and inferential statistical techniques with IBM SPSS Statistics. To satisfy the requirements for parametric testing, normality and linearity analyses were conducted beforehand. The Pearson correlation test identified a moderate yet significant positive relationship between the variables (r = 0.412, p = 0.001). These results indicate that students who demonstrate stronger digital literacy skills are more likely to achieve higher levels of English reading comprehension. The findings reinforce the value of incorporating digital literacy development into English instruction to support reading achievement in contemporary, technology-enhanced educational settings.